The Continuous Glucose Monitor as Boundary Object: How a Diabetic Device Reveals The Generalized Becoming-Diabetic of Quantified Selfhood - Rentschler, Carrie Ann (AoIR Selected Papers of Internet Research, 2026)
This talk examines how diabetic use of self-tracking continuous glucose monitors (CGMs) and diabetic data sensibilities that come from CGM use have been increasingly generalized to non-diabetic users and uses of CGM devices since 2021, when CGMs were approved in some international jurisdictions for use without requisite medical necessity. Communities of non-diabetic practice use the CGM to measure their glucose like diabetic users do, but in frameworks that both distance and re-center diabetes in their design and use. Just as diabetics learn to feel their numbers in relation to how CGMs datafy and visualize their glucose numbers over time, non-diabetic CGM users aim to measure, visualize, and develop a feel for their sugars like people with diabetes do: to develop diabetic-like “data gazes,” ways of seeing data about glucose that people with diabetes cultivate around the graphical visualizations of CGM data. CGM use by people without diabetes generalizes diabetic practice, technology, and sensibility, putting people with and without diabetes into newly configured, and often contentious, relations around their shared use of the CGM device. Based in analysis of social media marketing, online promotions, unboxing videos and a corpus of social media comments around CGM use by people without diabetes, this talk demonstrates how centrally chronic illness figures into the practices, routines and feel of quantified selfhood with the CGM, around the one chronic illness that stands in for managed chronic living more generally: diabetes.